The use of groin vault sections in Islamic and Mudejar architecture of Al-Andalus, North Africa and Sicily - Dokmak, Ahmed (Anales de Historia del Arte, 2010)
This article studies the use of sections of the groin vault as supporting architectural elements, particularly as squinches, its origin and development across the territories of Western Islam, particularly in the Iberian Peninsula. It includes a typological study supported on a broad catalogue of examples.